IMPLEMENTATION OF HABITUATION AND ASSIGNMENT METHODS IN CONGREGATIONAL PRAYER AND DHUHA PRAYER FOR MAN 1 STUDENT OF BOGOR REGENCY - Iskandar, Sofwan; Mujahidin, Endin; Hardianto, Budi (LPPM Univ. Ibn Khaldun Bogor, 2023)
The implementation of habituation and assignment of something good to students is something positive, especially what is accustomed to congregational prayer and dhuha prayer. This habituation will be very memorable in the minds and behavior of students. Including the assignment to be an imam, the reading of prayers after congregational prayers and dhuha prayers is more memorable than just religious knowledge. The implementation of this observation method shows that the habituation and assignment method for students at MAN 1 Bogor shows quite satisfactory results. For congregational prayers zhuhur and ashar 80% and for dhuha prayers reaching 90%, this is something extraordinary. MAN 1 Bogor whose students learn more religion than schools, such as high schools or vocational schools, has not been able to apply the habit of congregational prayer and dhuha prayer 100%. This is caused by several factors, one of which is diverse student input, and awareness for it has not been maximized. But the author is optimistic that if this method of habituation and assignment continues, it will become a habit for students in the future.